Pediatric Autoimmune Encephalitis: A Nationwide Study in Latvia - Pretkalnina, D.; Grinvalde, S.; Kalnina, E. (Neuropediatrics, 2024)
Background Autoimmune encephalitis (AE) is the third most common encephalitis in children. Diagnosis can be challenging due to overlapping and diverse clinical presentations as well as various investigation results. This study aims to characterize the clinical, diagnostic features, as well as treatment and outcomes of AE in children and determine the incidence of pediatric AE in Latvia.Methods The study was conducted at the Children's Clinical University Hospital in Riga. The study participants were patients under the age of 18 years diagnosed with AE from 2014 to 2022. Data regarding clinical characteristics, investigation findings, treatment strategy, and outcomes were retrospectively collected from the medical history data system.Results We included 18 pediatric patients diagnosed with AE. The mean incidence of pediatric AE in Latvia was 0.56 per 100,000 children. Most patients (66.6%) had seronegative AE. In the seropositive group, the most common was anti-methyl-D-aspartate receptor AE, with two patients having other antibodies. The most prevalent clinical features were personality change, cognitive impairment, autonomic dysfunction, and movement disorders. The majority of patients (58.8%) received first-line treatment only. More than half (55.6%) of our AE patient group had long-term sequelae.Conclusions Our study shows that the pediatric AE incidence in Latvia is similar to what has been previously reported in other studies. A relatively high proportion of seronegative AE was present in our cohort, indicating that awareness of possible misdiagnosis should be raised. Further research is needed to better understand the underlying mechanisms, characterize clinical features, and determine the treatment of choice in different situations to improve long-term outcomes.
Keywords: autoimmune encephalitis; NMDA; pediatric AE incidence